Analysis of the level of Islamic financial literacy among college students: Scoping review - Fitri, Yulita Eka (International journal of economic perspectives, 2026)
The global development of the Islamic economy continues to show encouraging growth. However, in Indonesia, Islamic financial literacy and inclusion remain relatively low. One major challenge is the gap between theoretical understanding and the application of Islamic financial products, particularly among university students. This study aims to evaluate students' level of knowledge regarding Islamic finance and their tendencies in managing personal finances, while also identifying factors that hinder the use of Islamic financial services. This study employed a scoping review method using the Google Scholar search engine. A total of seven articles were extracted. The results indicate that although students have a relatively good level of literacy and a high interest in the Islamic financial system, this has not been reflected in actual practice in daily life. These findings emphasize the need for increased educational efforts, more effective use of digital media, and increased accessibility of Islamic financial services among the younger generation.